A homozygous mutation in TRIM36 causes autosomal recessive anencephaly in an Indian family. (13th January 2017) - Singh, Nivedita; Kumble Bhat, Vishwanath; Tiwari, Ankana; Kodaganur, Srinivas G.; Tontanahal, Sagar J.; Sarda, Astha; Malini, K.V.; Kumar, Arun
Abstract: Anencephaly (APH) is characterized by the absence of brain tissues and cranium. During primary neurulation stage of the embryo, the rostral part of the neural pore fails to close, leading to APH. APH shows a heterogeneous etiology, ranging from environmental to genetic causes. The autosomal recessive inheritance of APH has been reported in several populations. In this study, we employed whole-exome sequencing and identified a homozygous missense mutation c.1522C > A (p.Pro508Thr) in the TRIM36 gene as the cause of autosomal recessive APH in an Indian family. The TRIM36 gene is expressed in the developing brain, suggesting a role in neurogenesis. In silico analysis showed that proline at codon position 508 is highly conserved in 26 vertebrate species, and the mutation is predicted to affect the conformation of the B30.2/SPRY domain of TRIM36. Both in vitro and in vivo results showed that the mutation renders the TRIM36 protein less stable. TRIM36 is known to associate with microtubules. Transient expression of the mutant TRIM36 in HeLa and LN229 cells resulted in microtubule disruption, disorganized spindles, loosely arranged chromosomes, multiple spindles, abnormal cytokinesis, reduced cell proliferation and increased apoptosis as compared with cells transfected with its wild-type counterpart. The siRNA knock down of TRIM36 in HeLa and LN229 cells also led to reduced cell proliferation and increased apoptosis. We suggest that microtubule disruption and disorganized spindles mediated by mutant TRIM36 affect neural cell proliferation during neural tube formation, leading to APH.